The degree Availability of Quality Assurance Standards in Teacher Preparation Program in Elementary Education in Aleppo University from the Viewpoints of the Involved in the Education College of the Aleppo University. - Mansour , Sumea; Samman , Zienb (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to identify the degree Availability of Quality Assurance Standards in Teacher Preparation Program in Elementary Education in Aleppo University from the Viewpoints of the Involved in the Education College of the Aleppo University, perspective, depending on the following variables (educational qualification; years of experience), Descriptive analytical methodology was used in this study, the study sample included(84) members of the Involved employees in the Education College of the Aleppo University for the academic year 2016-2017. To achieve the aim of this study, a questionnaire was designed, consisting of five study areas which included (65) paragraphs that expressing the employees’ views at the Involved in the Education College of the Aleppo University. The results showed that the degree Availability of Quality Assurance Standards in Teacher Preparation Program in Elementary Education in Aleppo University from the Viewpoints of the Involved in the Education College of the Aleppo University in the areas of the questionnaire were moderate ,the results exhibited significant differences according to the changing in the educational qualification among professor and professor assistant, while there were no significant differences materially depending on a variable number of years of experience as it came probability value greater than (0.05) at each axis of the axes of the degree of availability of quality assurance standards, and at the aggregate level, the level of confidence (95%) and (2.81 ) degrees of freedom, presented This research presented suggestions: activating the principle of transparent objectivity and questioning of all the faculty members; reconsidering the principle of acceptance to students; developing a curriculum of teacher preparation standards to include complementary decisions included general education, vocational side and Specialistic side; working to provide buildings, equipments and sources of appropriate workshops which all contribute to achieve a level of education quality.